1985
DOI: 10.1247/csf.10.339
|View full text |Cite
|
Sign up to set email alerts
|

Continuous fluorometric assay of Ca2+ transport by liposomes with Quin 2 entrapped: Effect of phospholipase A2 and unsaturated long-chain fatty acids.

Abstract: ABSTRACT. The amount of free calcium in the cytoplasm is important in stimulation coupled with a number of cellular functions. The putative iono-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In view of the above problems we have sought to develop a flexible and defined model system for investigating transport. The present system is an improvement over earlier vesicle-based systems (e.g., Pohl et al, 1980;Weissman et al, 1980;Blau et al, 1984;Smaal et al, 1985;Utsumi et al, 1985;Shastri et al, 1987;Blau and Weissman, 1988;Sokolove and Kestner, 1989;van Zanten et al, 1992;Walsh and Monbouquetle, 1993) in several ways. Preparation of loaded vesicles by freeze-thaw extrusion is straightforward and results in vesicles that are unilamellar, of relatively uni- a) -valinomycin 0.242 + 0.0005 25.2 + 0.3 b) + valinomycin 0.230 + 0.007 27.0 + 0.3 lonomycin a) -valinomycin 0.354 ± 0.011 31.6 ± 0.3 b) + valinomycin 0.398 + 0.002 32.4 + 0.2 4-BrA23187 a) -valinomycin 0.244 + 0.009 21.9 + 0.6 b) + valinomycin 0.260 + 0.008 27.5 + 0.6 All values are means + the SD (n = 5) obtained from experiments like those shown in Fig.…”
Section: Discussionmentioning
confidence: 72%
“…In view of the above problems we have sought to develop a flexible and defined model system for investigating transport. The present system is an improvement over earlier vesicle-based systems (e.g., Pohl et al, 1980;Weissman et al, 1980;Blau et al, 1984;Smaal et al, 1985;Utsumi et al, 1985;Shastri et al, 1987;Blau and Weissman, 1988;Sokolove and Kestner, 1989;van Zanten et al, 1992;Walsh and Monbouquetle, 1993) in several ways. Preparation of loaded vesicles by freeze-thaw extrusion is straightforward and results in vesicles that are unilamellar, of relatively uni- a) -valinomycin 0.242 + 0.0005 25.2 + 0.3 b) + valinomycin 0.230 + 0.007 27.0 + 0.3 lonomycin a) -valinomycin 0.354 ± 0.011 31.6 ± 0.3 b) + valinomycin 0.398 + 0.002 32.4 + 0.2 4-BrA23187 a) -valinomycin 0.244 + 0.009 21.9 + 0.6 b) + valinomycin 0.260 + 0.008 27.5 + 0.6 All values are means + the SD (n = 5) obtained from experiments like those shown in Fig.…”
Section: Discussionmentioning
confidence: 72%
“…We recently demonstrated that some unsaturated fatty acids increase the transport of calcium ion across liposomal membranes (37,38). Our results suggest that unsaturated fatty acids liberated from membranous phospholipids by phospholipase (3,5,11,40) enhance the mobilization of calcium and that the change in cellular calcium homeostasis modulates the Ca2+-related metabolism.…”
mentioning
confidence: 62%
“…Stimulation of superoxide generation by unsaturated fatty acids depended on their concentrations (Fig. 2), seemingly being proportional to their abilities to increase calcium transport across the liposomal membranes (37,38) (Fig. 3).…”
Section: And Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The accumulation of PLA 2 -produced products at the hydrolyzed region perturbed lipid packing, leaving space for water molecules to penetrate deeper into the lipid bilayer (Staneva et al, 2004). A lines of evidence demonstrated that PLA 2 could increase membrane permeability to H + , Ca 2+ and water (Eriksson and Saris, 1989;Donlon et al, 1979;Utsumi et al, 1985). The enzyme could also affect membrane potential (Cecchini et al, 2005) and membrane fluidity (Kinjo et al, 1988).…”
Section: Discussionmentioning
confidence: 99%